Penerapan Sistem Akuntabilitas dalam Penyusunan Laporan Keuangan Kinerja Instansi Sekretariat Daerah Kantor Bupati Deli Serdang - Mumtaz Muhammad Naufal; Laylan Syafina (AKUA: Jurnal Akuntansi dan Keuangan, 2024)
Implementation of an accountability system in preparing financial reports on agency performance refers to the use of a series of procedures and policies to ensure that all stages in the process of preparing financial reports are carried out to high and measurable standards. This research aims to determine and analyze the application of the accountability system in preparing performance financial reports for the regional secretariat of the Deli Serdang Regent's Office and to determine the inhibiting factors in implementing the accountability system in preparing performance financial reports at the regional secretariat of the Deli Serdang Regent's Office. The data collection methods are observation, interviews and documentation. The research results show that the implementation of this system has significantly increased transparency and accuracy in preparing financial performance reports. A well-documented process makes auditing and verification easier, so that the information presented in the report is more complete and clear. Factors inhibiting the implementation of an accountability system in preparing financial reports include a lack of human resources trained in financial accountability, especially in timely financial management and reporting, as well as inadequate technological infrastructure.